If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -16 = 3x Reorder the terms: -16 + 10x = 3x Solving -16 + 10x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -16 + 10x + -3x = 3x + -3x Combine like terms: 10x + -3x = 7x -16 + 7x = 3x + -3x Combine like terms: 3x + -3x = 0 -16 + 7x = 0 Add '16' to each side of the equation. -16 + 16 + 7x = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 7x = 0 + 16 7x = 0 + 16 Combine like terms: 0 + 16 = 16 7x = 16 Divide each side by '7'. x = 2.285714286 Simplifying x = 2.285714286
| 12y-7y-9=60.90 | | 6(x-2)+6=6 | | 500-20w= | | 2+9=2+3x-2x | | 4(6a+6)=-8(-5a-9) | | 2(x-1)=2(x-1) | | 2.25x+4.50=1.75x+6 | | 8s-16-5s=-5 | | 10-x=3(x-6) | | 6-a/3=2 | | 6+2.5+6+2.5= | | 0.7x+0.6(12-x)=47 | | 7+4p=19 | | F(h(x))=x^2+7 | | V-4=5+5v+3 | | 29=-9v+9-v | | -9m-3=78 | | 5+x-4x=-1 | | 8x-2(3x-5)=3x+15 | | -3-8x=-10-2x-7x | | 2x-5(x-4)=-3+4x-12 | | -6b-8=19 | | 4g-6-9=3 | | 3=5-2a | | 8x-1=8(x-3) | | 5x+8(-4x-9)=-10(-2x-9)+26 | | x^2-6x-96=0 | | 2k-1=-5+3k | | 24x=24+7x | | -3(4p+4)-2(6-14p)-3(7+5p)=0 | | 2(-5U+10)+2u= | | 2-5a=-8 |